International Conference on Reinvention of Local Tradition and New Technologies for Sustainability / Nor Azizah Talkis - Talkis, Nor Azizah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
UiTM Perak Branch successfully co-organised the International Confer-ence on Reinvention of Local Tradition and New Technologies for Sustain-ability (ICRP – AVAN 2017). The main organis-er, Universitas Syiah Kua-la (UNISYIAH) played host for this conference which was held from Oc-tober 18 to 19, 2017 in Acheh, Indonesia. throughout this conference, notable scholars; Prof. Regan Potangaroa, Assoc. Prof. Sr. Dr. Md. Yusof Hamid and Prof. Naka Ryusuke were invited as keynote speakers along with the Mayor of Surabaya himself, Tri Rismaharini. The diverse backgrounds of these presenters have successfully outreached wider perspectives in achieving the aim of the conference in sharing the latest researches with the communities.